ДЕЙСТВУЮЩЕЕ ЗАКОНОДАТЕЛЬСТВО, РЕГУЛИРУЮЩЕЕ ПРОВЕДЕНИЕ АЗАРТНЫХ ИГР В РЕСПУБЛИКЕ МОЛДОВА И В ЗАРУБЕЖНЫХ СТРАНАХ - Сосна, Б., Здоров Ю. (SUPREMANCE OF LAW, 2017)
The authors attempted to analyze the legislation of the Republic of Moldova on gambling compared with the laws of foreign countries and to make proposals to improve the legislation of the Republic of Moldova.
Keywords: budget; gambling; lottery; casino; slot machines; bookmaking; bingo; telecommuni-cationsgamble